Current state of affairs in pulse-periodic generation of microwave radiation high-power nanosecond CM-wave pulses; The 17th International Crimean Conference Microwave and Telecommunication Technology, Sevastopol, Crimea, september 10-14, 2007; Vol. 2 - Afanasyev K. V.; Bykov N. M.; Yeltchaninov A. A.; Klimov A. I.; Kovalchuk O. B.; Kutenkov V. O.; Rostov V. V.; Mesyats G. A. Gennady Andreyevich; Shpak V. G.; Yalandin M. I. (2007, 2007)
В фонде НТБ ТПУ отсутствует